Business Model Improvement: A Study Case of Channeling through E-commerce - Silvy Anita Theresia Sitorus; Avanti Fontana (AIBPM Publisher, 2021)
Micro, Small, and Medium Enterprises or MSMEs contribute to domestic economic growth. However, in the course of business, MSMEs still have obstacles. From the standpoint of internal, namely aspects of non-financial capacity such as management, personnel, marketing, and production, as well as financial aspects such as access to sources of financing, profitability management, and profit growth. External factors, namely political, economic, social, technological, and health situations, have an impact on the stability of business performance. Advances in technology, supported by infrastructure and ease of regulation, have encouraged the growth and development of digital-based businesses. This business coaching method focused on the activities at XYZ's Crackers Business, an Indonesian MSME. The purpose of this business coaching activity is to develop marketing channels for XYZ businesses. Data was collected through interviews, observations and surveys. The data is then collected and analyzed through Business Model Canvas analysis, SWOT and TOWS Business Model Canvas analysis, PESTEL analysis, market opportunity analysis (STP), Marketing Mix analysis, and Gap analysis. The solution obtained is to improve the business model, namely the channel element in the form of adding an online store through e-commerce.